Pengembangan Media Edubuddy Menggunakan Ren’py untuk Meningkatkan Keterampilan Membaca Nyaring Siswa Kelas II Sekolah Dasar - Nusantara, Ananda; Sukasih, Sri; Sukardi, Sukardi (LPPM Politeknik Raflesia, 2023)
Based on research data conducted at SD Negeri 04 panggang, Jepara Regency. There are problems in Indonesian language learning related to the low language skills of students in reading aloud skills, as well as the lack of variety in the teaching media used. Based on these problems, this research aims to develop, test the feasibility, and test the effectiveness of Edubuddy media using Ren'py. Ren'py is a free game creation engine where creators can make visual novel genre games. This research is development research (R&D) using the ADDIE development paradigm. The subjects of this study were 29 grade II students, grade II teachers, and a team of experts (media, material, and learning practitioners). The data collection techniques used were observation, interviews, documentation, questionnaires and tests. Data analysis techniques were feasibility analysis, teacher and student responses, t-test and N-Gain. The results showed that Edubuddy media was very feasible with a percentage of material expert assessment of 86.6%, media experts of 82.8%, learning practitioners of 89.4%, teachers and students of 98.6% and 100%. The effectiveness of the product uses sig (2-tailed) with a p value of 0.00 <0.05, there is a difference in pre-test, post-test results. The N-Gain test is 0.37 with moderate criteria, there is an increase in the average pre-test, post-test. Therefore, Edubuddy media is effective, efficient and feasible to use in learning because it can improve the reading skills of grade II elementary school students.